DESIGN AN IOT-BASED SMART DOOR CONTROL AT THE PRDP OFFICE OF UNIVERSITAS PEMBANGUNAN PANCA BUDI - Horas Ringkot Sihombing; Hamdani; Solly Aryza (INFOKUM, 2022)
In this research, a security system was designed to control the entrance through a smart device in Gedung I floor 4 PRDP office which the office is a part of Universitas Pembangunan Panca Budi located at Jl. Jend. Gatot Subroto No. Km, 4.5 Sei Sikambing, Medan Sunggal disctrict, Medan City, North Sumatra, 20122. Smart device in this case known as smart lock door which can facilitate humans in many ways included increasing the security of a room. This can be worked with the concept called the Internet of Things. This research designed a room security control system in which the operation used an RFID card or manually system called Smart lock door. The main function of this device is to limit people who can access the door and can be monitored remotely so that office security can be securred. In designing this smart door control system, the main supporters use Arduino Nano as a control center, Wemos D1 mini as a microcontroller and monitoring board connected to WIFI. The basic principles can be used optimally, effectively, efficiently and ensure the safety of its users..